The Effects of Physical Training on Quality of Life, Aerobic Capacity, and Cardiac Function in Older Patients With Heart Failure: A Meta-Analysis - Slimani, Maamer; Ramirez-Campillo, Rodrigo; Paravlic, Armin; Hayes, Lawrence D.; Bragazzi, Nicola Luigi; Sellami, Maha (Frontiers in Physiology, 2018)
Aim: The purposes of this meta-analysis were to quantify the effectiveness of physical training on quality of life (QoL), aerobic capacity, and cardiac functionin older patients with heart failure (HF) and evaluate dose–response relationships of training variables (frequency, volume, and duration). Methods: Scholarly databases (e.g., PubMed/MEDLINE, Google Scholar, and Scopus) were searched, identifying randomized controlled trials that investigated the effectiveness of different training modes on QoL (assessed by the Minnesota Living with Heart Failure Questionnaire), aerobic capacity (assessed by the 6 min walk test) and cardiac function (assessed by left ventricular ejection fraction). Results: Twenty five studies were included with a total of 2,409 patients. Results showed that exercise training improved total QoL (small ES = -0.69; 95 % CI -1.00 – 0.38; p < 0.001), aerobic capacity (small ES = 0.47; 95 % CI 0.15 – 0.71; p = 0.002) and cardiac function (moderate ES = 0.91; 95 % CI 0.37 – 1.45; p = 0.001). In addition, univariate analyses revealed the moderating variable ‘training mode’ significantly influenced aerobic capacity (Q = 9.97; p = 0.007), whereby, resistance training had the greatest effect (ES = 1.71; 95 % CI 1.03 – 2.39; p < 0.001), followed by aerobic training (ES = 0.51; 95 % CI 0.30 – 0.72; p < 0.001), and combined training (ES = 0.15; 95 % CI -0.24 – 0.53; p = 0.45). Meta-regression analysis showed that only the duration of an intervention predicted the effect of physical training on QoL (coefficient = - 0.027; p = 0.006), with shorter training durations (12 weeks) showing larger improvements. Conclusion: The present meta-analysis showed that physical training has positive effects on QoL, aerobic capacity, and cardiac function in older patients with HF. Practitioners should consider both training volume and mode when designing physical training programs in order to improve QoL and aerobic capacity in older patients with HF.